In the Heights [videorecording (Blu-Ray)] - Miranda, Lin-Manuel, 1980- (Warner Bros. Entertainment, 2021)
The likeable, magnetic, bodega owner Usnavi saves every penny from his daily grind as he hopes, imagines, and sings about a better life. Meanwhile, his tight-knit community faces the challenge of gentrification, losing their homes while trying to better themselves and hold on to their cultures.